Iklim Komunikasi Keorganisasian - Harjana, Andrë A. (Jurnal ILMU KOMUNIKASI, 2007)
Abstract: Organizational communication climate has become a major concept in organizational communication since it was coined by W. Charles Redding in 1972. Its conceptual origin, however, goes back to the much earlier work of of Chester Barnard (1938). Numerous research works since early 1970’s have empirically tested its position as a major variable for organizational effectiveness. It is now assumed that communication climate is the sine qua non for effective organizational management. This article traces the development of our understanding of the concept through the works of two different schools of thought, namely the functionalist and the interpretivist ones. Implications for future research are carefully described.